Selective removal of nitrate using a novel asymmetric amine based strongly basic anion exchange resin - Yue Sun; Weisheng Zheng; Xinchun Ding; Rajendra P Singh (Adsorption Science & Technology)
In this study, a novel asymmetric amine-based strongly basic anion exchange resin SE-1 was synthesized successfully via the reaction of chloromethylated styrene–divinylbenzene copolymer with N , N -dimethyloctylamine. The sorption performance of SE-1 for selective removal of nitrate in aqueous solution was compared to a commercially available nitrate specialty resin, namely Purolite A 520E (A 520E). It was found that the kinetic data could be described better by the pseudo-second-order model, and SE-1 indicated a faster sorption kinetics than A 520E resin. The Langmiur model was more appropriate for explicating the sorption isotherm. Importantly, SE-1 exhibited a greater sorption capacity for nitrate regardless of the absence or presence of competing anions in solutions. The result of column tests reinforced the feasibility of SE-1 for practical application in groundwater treatment.